(untitled) (Quaderni di Gargnano, 2020)
The contribution dwells on the treatment of rhyme in Sonetti et canzoni, highlighting the decisive role played by the Petrarchan model in a fundamental sector of poetic composition: it highlights the tendency to take up series of rhymes with the precise intention of creating a reference to Petrarch’s texts, the adherence to the model in the choice of rhyming vocabulary and the fidelity to the lesson of Rerum vulgarium fragmenta in the preference given to phonically relevant rhymes and in the attempt to avoid banal solutions. It is also highlighted the tendency of Sannazaro to use the connections between the rhymes for the construction of the sonnet, metric genre in which the rate of creativity appears less high. Il contributo si sofferma sul trattamento nella rima nei Sonetti et canzoni, evidenziando il ruolo decisivo svolto dal modello petrarchesco in un settore fondamentale della composizione poetica: viene messa in risalto sia la tendenza a riprendere serie di rime con la volontà precisa di creare un richiamo a testi di Petrarca sia l’aderenza al modello nella scelta del lessico in rima sia la fedeltà alla lezione dei Rerum vulgarium fragmenta nella preferenza accordata a rime fonicamente rilevate e nel tentativo di evitare le soluzioni più banali. Si mette in luce inoltre la tendenza di Sannazaro a servirsi dei richiami tra le rime per la costruzione del sonetto, genere metrico nel quale il tasso di creatività appare meno alto che nella canzone.